P14.90 Interleukin 6 is a useful marker for pseudotumoral inflammatory CNS lesions suspicious of lymphoma. (6th September 2019) - Ungureanu, A; Costopoulos, M; Parratte, T; Brinet, A; Durand, H; Gaultier, C; Postert, T; Hurstel, R; Alamome, I; Sellal, F; Le Garff-Tavernier, M; Ahle, G
Abstract: BACKGROUND: Interleukin (IL)-6 is a dual pro and anti-inflammatory cytokine and its presence in the cerebrospinal fluid (CSF) is considered as a marker of central nervous system (CNS) inflammation. Our aim was to analyze the diagnostic significance of CSF IL-6 levels among various CNS pseudotumoral inflammatory lesions (PIL) and primary CNS lymphoma (PCNSL). MATERIAL AND METHODS: We retrospectively analyzed the CSF IL-6 concentrations in 43 patients with a differential diagnosis of PCNSL. Finally, 28 patients were positively diagnosed with PCNSL and 15 with other inflammatory CNS disorders. We verified the results with CSF IL-10, a biomarker for PCNSL. IL concentrations were measured by flow cytometry using the cytometric bead array (CBA) technique (BD Biosciences) with a detection limit set at 2.5 pg/ml. RESULTS: In the PCNSL group, the median CSF IL-6 concentration was 8 pg/ml, interquartile range (IQR) 5 - 18.5. For the patients with other PIL the median concentration was of 70 pg/ml, IQR 5 - 1368. A group comparison disclosed significantly higher CSF IL-6 levels in patients with PIL compared to the group with PCNSL (p=0.032). Moreover, IL-6 was correlated with CSF cell count for the whole cohort (r=0.45, p=0.002), as well as for the PIL group (r=0.56, p=0.028), but not for the PCNSL group (r=0.3, p=0.13). We found significantly higher CSF IL-10 levels in patients with PCNSL compared to the group with other CNS inflammatory lesions (p<0.001). CONCLUSION: Our study suggests that CSF IL-6 levels could represent, in addition to CSF IL-10, a useful biomarker in the diagnosis of CNS PIL that may mimic PCNSL.